Art Therapy With Jewish Ultra-Orthodox Children: Unique Characteristics, Benefits, and Conflicts - Doron, Einat (Frontiers in Psychology, 2020)
Abstract The present paper presents the potential benefits and conflicts of the encounter between Jewish ultra-orthodox children – belonging to a closed and segregated group - and art therapy – with its cultural, Western, secular and professional characteristics. The paper describes the complex interface between the therapeutic use of art as a form of free expression and religious commandments and restrictions. The dialogue between art, therapy, and cultural religious boundaries is described through a case study of an eight-year-old ultra-orthodox boy and a secular female art therapist. Issues such as self-expression, gender roles, and identity exploration are discussed, emphasizing the unique characteristics, benefits and conflicts of such an encounter.